Palm oil: still the best choice - Abdullah, Dzulkefly Kuang (Universiti Putra Malaysia Press, 2008)

(untitled)
Looking at the development of the palm oil market today it is conceivable that this oil is going to be the world’s choice. The continuing high demand for it, as seen in the world market today, reflects the importance of palm oil and the public’s awareness of its superiority. Palm oil is extracted from the fruits of oil palm (Elaeis guineensis), the golden crop of Malaysia. Oil from this attractive palm has been used as food and energy source for millennia. Palm oil can be processed to produce various type of solid fats and liquid oils of different physical and chemical properties, while this cannot be done with other vegetable oils. Being trans fatty acid free, and possessing significant nutritional and medicinal values, palm oil is chosen for better health. It is packed with nutrients; pro-vitamin A, vitamin E, phytosterol, squalene, coenzyme and lecithin. Probably, the most exciting discovery is that palm oil has shown effective anti cancer activity and is a cholesterol lowering agent. Scientists and nutritionists, backed by extensive published papers agree that tocotrienols, found only in palm oil, are effective anti cancer agents and have been shown to inhibit human breast cancer cells whereby gamma-tocotrienol is 3 times more potent in inhibiting the growth of human breast cancer cultured-cells than Tamoxifen (a drug widely used in the treatment of breast cancer). While palm oil has all these beneficial values, none of the other vegetable oils possess similar qualities. In the current biofuel era, palm oil is touted to be the best choice for biofuel feedstock. Based on its availability and fuel-related properties, today palm oil is the most viable raw material for biodiesel conversion. However, the existing Government policy will restrict future production of palm oil for biodiesel in anticipation of strong world demand for biodiesel raw materials. Since biodiesel production from palm oil will be limited in the future, the Government should look for alternative renewables, probably bioethanol from cassava as a complement to biodiesel, and at the same time explore new technologies particularly to convert plant celluloses or palm biomass to bioethanol. Being a tropical country, Malaysia has an abundance of plants where celluloses can be extracted and used as raw materials for bioethanol.